The effect of speed on Achilles tendon forces and patellofemoral joint stresses in high-performing endurance runners - Starbuck, C.; Bramah, C.; Herrington, L.; Jones, R. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Achilles tendinopathy and patellofemoral pain are common running injuries associated with increased Achilles tendon (AT) forces and patellofemoral joint (PFJ) stresses. This study examined AT forces and PFJ stresses at different running speeds in high-performing endurance runners. Twenty runners ran overground at four running speeds (3.3, 3.9, 4.8, and 5.6 m/s). AT forces and PFJ stresses were estimated from kinematic and kinetic data. Repeated measures ANOVA with partial eta squared effect sizes was conducted to assess differences between running speeds. Increased peak AT forces (19.5%; p < 0.001) and loading rates (57.3%; p < 0.001) from 3.3 m/s to 5.6 m/s were observed. Cumulative AT loading was greater in the faster speeds compared to the slower speeds. Faster running speeds resulted in increased peak plantar flexor moments, increased peak plantar flexion angles, and a more flexed knee and an anterior center of pressure position at touchdown. Peak PFJ stress was lower in the slowest speed (3.3 m/s) compared to the faster running speeds (3.9-5.6 m/s; p = 0.005). PFJ stress loading rate significantly increased (43.6%; p < 0.001). Greater AT loading observed could be associated with strategies such as increased plantar flexor moments and altered lower body position at touchdown which are commonly employed to generate greater ground contact forces. Greater AT and PFJ loading rates were likely due to shorter ground contact times and therefore less time available to reach the peak. Running at faster speeds could increase the risk of developing Achilles tendinopathy and patellofemoral pain or limit recovery from these injuries without sufficient recovery.